2003
DOI: 10.1046/j.1464-410x.2003.04277.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors correlate with prostate size in men with bladder outlet obstruction

Abstract: tested. The measured variables were assessed statistically in relation to whether the prostate volume was smaller (22 men) or larger (30 men) than 50 mL. RESULTSPatients with a large prostate (mean 104 mL) had a higher mean arterial pressure (105 vs 95 mmHg, P < 0.01), and serum glucose (5.3 vs 4.8 mmol/L, P < 0.01) and serum cortisol (423 vs 362 nmol/L, P = 0.06) concentrations than those with a small gland (mean 31 mL). The personality test showed that they were also less assertive than the others ( P < 0.03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…As CVD have a high incidence of morbidity and mortality, it is important to find patients at risk [3]. Previously, it has been suggested that LUTS are associated with CVD and may predict subsequent cardiovascular events [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As CVD have a high incidence of morbidity and mortality, it is important to find patients at risk [3]. Previously, it has been suggested that LUTS are associated with CVD and may predict subsequent cardiovascular events [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Methods We performed post hoc analyses using data from the Krimpen study, a large community-based study in the Netherlands. All men aged 50-75 years, without prostate or bladder cancer, a history of radical prostatectomy, or This may be explained by the fact that LUTS and CVD share risk factors such as obesity, diabetes, hypertension, smoking, and aging [4][5][6][7][8][9]. These well-known vascular risk factors might also impact LUTS through various pathways from vascular diseases [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations